Plan of the Baie de Castries on the eastern coast of Tartary in lat. 51 [degrees] 29' n. long. 139 [degrees] 39' e. of Paris : Discovered in 1787. - Bernizet, Sébastien. (William L. Clements Library Image Bank, 1790)
Pen and ink and watercolor chart of the area around De Kasrti, Khabarovsk Kary, on Tatarskiy Proliv opposite Sakhalin Island.; Printed map of the identical area by Bernizet appears in: Lapérouse, Jean François. Voyage de La Pérouse. 1797. Pl. 52.